Implementasi Reflektor Jalan Berbasis Pipa Semen sebagai Upaya Peningkatan Keselamatan di Jalur Perbukitan Nagari Sungai Jambur - Alda Laila Pertiwi; Fajar Hasidik; Nindi Audia; Rona Uli Sihotang; Tiara Anggaeny (Jurnal Kendali Teknik dan Sains, 2026)
Road user safety is a crucial aspect of transportation infrastructure development, particularly in hilly areas where accident risks are higher than in flat areas. Sungai Jambur Village is a hilly area with winding roads, minimal lighting, and limited road safety facilities. These conditions have the potential to increase the risk of accidents, particularly at night and during inclement weather. This article discusses the implementation of cement pipe-based road reflectors as a simple, economical, and easy-to-implement innovation to improve road user safety in the area. The method used in writing this article is a descriptive study with a field observation approach and a literature review related to transportation safety. The results of the discussion indicate that the use of cement pipe-based road reflectors can improve driver visibility, help mark bends and road edges, and have a positive impact on traffic safety in the hilly areas of Sungai Jambur Village. In addition, the use of local materials in the form of cement pipes makes this program more efficient and sustainable.